La literatura como castigo: sobre los problemas y contradicciones de la enseñanza de la literatura en los colegios públicos peruanos - Garvich Rebatta, Javier (2011)
ThePeruvian education level is very poor and it is nota secret. Even more it is nota secret the need of an important outlay to reconstruct -once again- the building of our educational system over the debris of three generations. However, the significant educational changes are not only produced by capital injections. We have forgotten that the curricular structure was imposed by theWorld Bank and if we demand for a better education for our children, it will be necessary to review it. The current teaching of literature, regarding content, particularly its praxis, is agood example.